2019
DOI: 10.1186/s12885-019-6237-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved clinical outcome using transarterial chemoembolization combined with radiofrequency ablation for patients in Barcelona clinic liver cancer stage A or B hepatocellular carcinoma regardless of tumor size: results of a single-center retrospective case control study

Abstract: BackgroundTo determine the safety and efficacy of transarterial chemoembolization (TACE) combined with radiofrequency ablation (hereafter, TACE-RFA) in treating Barcelona Clinic Liver Cancer (BCLC) Stage A or B (hereafter, BCLC A/B) hepatocellular carcinoma (HCC) patients, and to explore the range of tumor sizes suitable for combination therapy.MethodsThis retrospective study assessed the consecutive medical records of HCC patients with BCLC A/B who received TACE-RFA or TACE from September 2009 to September 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…A string of image-guided percutaneous ablations encompasses a great variety of techniques, including radiofrequency ablation (RFA), microwave ablation (MWA), ethanol injection, and cryoablation [ 62 65 ]. As RFA is the most frequently used ablation modality for HCC [ 66 , 67 ], the main topic addressed in this section is RFA.…”
Section: Methodsmentioning
confidence: 99%
“…A string of image-guided percutaneous ablations encompasses a great variety of techniques, including radiofrequency ablation (RFA), microwave ablation (MWA), ethanol injection, and cryoablation [ 62 65 ]. As RFA is the most frequently used ablation modality for HCC [ 66 , 67 ], the main topic addressed in this section is RFA.…”
Section: Methodsmentioning
confidence: 99%
“…TACE was performed according to our institutional standard protocol, which has been previously reported [ 20 ]. All operators had at least five years of experience in performing TACE procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The RFA procedure was performed in accordance with the standard treatment regimen described in our previous study [ 20 , 22 ]. In brief, following analgesia (10 mg of morphine) and local anaesthesia (5–10 mL of lidocaine), the electrode needle was inserted into the tumour nodule under the guidance of ultrasound or computed tomography (CT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, if the initial decision in this patient is to pursue TACE, there is emerging evidence from several Asian centers that combination therapy with TACE followed by RFA in BCLC A and B patients with HCC larger than 3 cm is generally safe and leads to superior overall and progression-free survival compared with TACE alone. (86)(87)(88)(89)(90)(91)(92) Chu et al (91) showed improved outcomes in patients undergoing combination TACE-RFA for a single 3.1-5 cm HCC compared with either modality alone. In a recent single-center retrospective analysis of 128 patients undergoing TACE-RFA compared with 271 receiving TACE alone, Ren et al (87) found improved overall and progression-free survival at 5 years, not only for patients with tumor diameter of 3.1-5 cm, but also for those with tumors larger than 5 cm as well.…”
Section: Choosing Among Lrt Optionsmentioning
confidence: 99%